Fiscal Equalisation in OECD Countries - Blöchliger, Hansjörg (OECD Publishing, 2007)
Fiscal equalisation is a transfer of fiscal resources across jurisdictions with the aim of offsetting differences in revenue raising capacity or public service cost. Its principal objective is to allow sub-central governments to provide their citizens with similar sets of public services at a similar tax burden. Fiscal equalisation can be seen as the natural companion to fiscal decentralisation as it aims at correcting potential imbalances resulting from sub-central autonomy. If sub-central governments had no fiscal power, no fiscal equalisation would be needed. Distinct fiscal equalisation arrangements first emerged during the 1940s and 1950s in a number of federal countries, and today most OECD Member countries have introduced some explicit or implicit fiscal arrangement that reduces fiscal disparities across jurisdictions. The significance of fiscal equalisation is highlighted not only by its extensive use in both federal and unitary countries, but also by the fact that its objectives and principles are often laid down in the constitution and hence form a central pillar of national fiscal policy
Keywords: Taxation